2020
DOI: 10.1042/bcj20200515
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of mitochondrial alternative oxidase in the appendices of Arum maculatum

Abstract: Cyanide-resistant alternative oxidase (AOX) is a nuclear-encoded quinol oxidase located in the inner mitochondrial membrane. Although the quality control of AOX proteins is expected to have a role in elevated respiration in mitochondria, it remains unclear whether thermogenic plants possess molecular mechanisms for the mitochondrial degradation of AOX. To better understand the mechanism of AOX turnover in mitochondria, we performed a series of in organello AOX degradation assays using mitochondria from various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…The findings further pinpoint to the beneficial role of AOX for plant resilience that is related to both ROS/RNS equilibration and redox homeostasis, able to avoid acidification and excess of toxic ethanol, and regulating at the same time adaptive energy supply for growth performance [( 21), in press, (77), preprint]. Interestingly, Ito et al (85) discovered in Arum that temperature-dependent switching between critical AOX polymorphisms in the binding site for AOX-pyruvate can determine energy-related metabolic regulation, which in turn results in plant performance. This striking finding underlines again the multifunctional role of AOX that includes besides ROS/RNS equilibration adjusting energy metabolism at the threshold between mitochondrial respiration and aerobic fermentation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings further pinpoint to the beneficial role of AOX for plant resilience that is related to both ROS/RNS equilibration and redox homeostasis, able to avoid acidification and excess of toxic ethanol, and regulating at the same time adaptive energy supply for growth performance [( 21), in press, (77), preprint]. Interestingly, Ito et al (85) discovered in Arum that temperature-dependent switching between critical AOX polymorphisms in the binding site for AOX-pyruvate can determine energy-related metabolic regulation, which in turn results in plant performance. This striking finding underlines again the multifunctional role of AOX that includes besides ROS/RNS equilibration adjusting energy metabolism at the threshold between mitochondrial respiration and aerobic fermentation.…”
Section: Resultsmentioning
confidence: 96%
“…ACE2 (Angiotensin-converting enzyme 2), TMPRSS2 (transmembrane protease serine 2) gene expression was not detected in the analysis and genes were not denoted in the Supplementary Table S6. this context, it is also pertinent to mention that recently an AOXdegrading protein has been discovered that might be added as a tool in potential AOX-based therapies (85).…”
Section: Resultsmentioning
confidence: 99%
“…The findings further pinpoint to the beneficial role of AOX for plant resilience that is related to both ROS/RNS equilibration and redox homeostasis, able to avoid acidification and excess of toxic ethanol, and regulating at the same time adaptive energy supply for growth performance (21, in press, 84). Interestingly, Ito et al (85) discovered in Arum that temperature-dependent switching between critical AOX polymorphisms in the binding site for AOX-pyruvate can determine energy-related metabolic regulation, which in turn results in plant performance.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, whether AOX could be useful in therapy as proposed for mitochondrial respiratory deficiency diseases (110)(111)(112)(113)(114)(115)) will, in our view, crucially depend on its adaptive (positive and negative) regulation, which includes also interaction with endophytes. In this context, it is also pertinent to mention that recently an AOX-degrading protein has been discovered that might be added as a tool in potential AOX-based therapies (85).…”
Section: Resultsmentioning
confidence: 99%
“…This role requires managing ROS/RNS increase and channeling energy and substance flow from fermentation when carbohydrate storages are released and enzymes get into motion (Saleh and Kalodimos, 2017), but the respiration chain is still structurally restricted and overloaded at massively incoming oxygen. AOX is mainly regulated by pyruvate (Millar et al, 1996, Hoefnagel et al, 1997, Albury et al, 2009, Hakkaart et al, 2006, Carré et al, 2011, Selinski et al, 2018) and, strikingly, Ito et al (2020) showed in Arum that energy-related metabolic regulation can be determined by temperature-dependent switching between AOX polymorphisms in the binding site for AOX-pyruvate. In this scenario, it might be of interest that AOX was essential in ethylene-induced drought tolerance and mediating autophagy generation via balancing ROS levels (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%